ANALISIS MODEL PEMBAHARUAN HUKUM ISLAM DI INDONESIA MELALUI WASIAT WAJIBAH - Irsan; Aslati Aslati; Khairunnas Jamal (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
ABSTRACT This research aims to analyze the model for reforming Islamic law in Indonesia through mandatory wills. This research is library research. The primary data for this research is the text of the Compilation of Islamic Law Article 209 paragraphs 3 and 4: "...... ...... to adoptive parents who do not accept a will, they are given a mandatory will of up to 1/3 of the child's inheritance. pick it up." "Adopted children who do not receive a will are given a mandatory will of up to 1/3 of their adoptive parents' inheritance." The data analysis technique in this research is content analysis. This research concludes that, first, renewal of Islamic law is the process of changing qabilah littaghayyur (subject to change) laws from old laws to new laws through a process of ijtihad based on considerations of 'urf (customary customs), benefits and legal analogy. Second, the model for reforming Islamic law through obligatory wills is to take into account the 'urf (customs) of society and the benefits of adopted children or adoptive parents. Third, the model of renewing Islamic Law in Indonesia through a mandatory will is not relevant to the concept of establishing Islamic Law, because the customs and customs of the community which are taken into consideration in determining a wajiabh will differ from the Al-Qur'an and Sunnah, and the benefit of the adopted child or adoptive parents which is the The considerations for determining a mandatory will conflict with the provisions for calculating inheritance that have been determined based on the Al-Qur'an and Sunnah, and at the same time these benefits conflict with other, greater benefits, namely the benefits of the heirs. Keywords: renewal model, Islamic law, mandatory will.